Demography and Provisions for Retirement: The Pension Composition, an Equilibrium Approach - Bernard M. S. van Praag; J. Peter Hop (Tinbergen Institute, 2018)
Pensions may be provided for in a modern society by several methods, viz., voluntary individual savings, mandatory fully funded occupational pension systems, and mandatory social security financed by pay-as-you-go. The specific mixture of the three systems we will call the pension composition. We assume that individual workers decide about their own individual savings, that the fully funded occupational system is decided upon by the age cohort of the median worker and that social security is decided upon by the median voter. For a given demography and interest rate the joint result of those decisions is a Pareto- equilibrium. Nowadays most of capital supply stems from individual and institutionalised pension savings. For ease of exposition we will assume that individual and collective pension savings are the only source of capital supply. When capital supply equals demand from industry there is equilibrium on the capital market with a corresponding equilibrium interest rate. In this paper we assume a demography with hundred age brackets and we investigate how changes in the birth and survival rates affect the pension composition and the capital market equilibrium. Our conclusion is that the demographic effects are considerable not only for the resulting pension composition, but also for macro-economic variables as the wage rate, the interest rate and the capital-income ratio. It follows that the pension composition in general and social security in particular is determined by the demography and cannot be used as long-term political instrument. We find that this is relevant for the present century, where birth and mortality rates in most western countries are steeply declining.
Keywords: H55; H75; J1; J26; 330; demography; funded pensions; unfunded pensions; social security; interest rate; overlapping generations; individual savings